Clinical characteristics of adults with alcohol dependence syndrome comorbid with antisocial personality disorder: a cross-sectional study - Jarcuskova, Dominika; Pallayova, Maria; Carnakovic, Simona; Frajka, Maria; Fidmik, Jan; Bednarova, Aneta (Frontiers in Psychiatry, 2024)
Introduction: Antisocial Personality Disorder (ASPD) is characterized by a pervasive pattern of disregard for and violation of the rights of others, typically emerging by age 15 years and involving behaviors such as deceitfulness, impulsivity, and aggressiveness. The present study sought to examine the prevalence of the comorbid ASPD in adult people with Alcohol Dependence Syndrome (ADS) and identify clinical characteristics associated with ASPD.A cross-sectional study of 100 consecutive subjects diagnosed with ADS was conducted. Subjects were examined between August 2023 and September 2023. Various assessments and questionnaires were employed, including the Montreal Cognitive Assessment (MoCA), Alcohol Use Disorders Identification Test (AUDIT), and Structured Clinical Interview for DSM-IV (SCID-II). A computed tomography (CT) scan of the brain was performed on 47.5% participants.Results: Out of the 100 individuals screened for the study, 20 were excluded. The study found that 35% of the examined study participants had a comorbid ASPD. Individuals with both ADS and ASPD were more likely to be younger, started drinking at an earlier age, had higher hospitalization rates, and scored higher on the AUDIT test (all P < 0.05%). Also, they had lower education levels, higher rates of unemployment, and lower marriage rates (all P < 0.05%). In addition, they reported more family members with ADS, incarceration, or mental illness and a higher frequency of traumatic experiences (all P < 0.05%). Depression, anxiety, stress (all P < 0.05%), and sleep problems (P = 0.058) were correlated with ASPD. Participants with the comorbid ASPD had lower MoCA scores (P = 0.046) and struggled with attention and linguistic subtests compared to subjects with ADS only.The study highlights the high prevalence of comorbid ASPD in participants with ADS, shedding light on their demographic and psychometric characteristics. Individuals with the comorbid ASPD are more likely to face cognitive deficits, especially in linguistic and attention-related tasks. The findings underline the importance of considering the comorbidity of ASPD in ADS subjects. The study implies that the understanding of the associated risk factors can aid in developing more targeted treatment interventions.